A new subspecies of Bracon pallicarpus Thomson, 1892 (Hymenoptera, Braconidae, Braconinae) parasitising larvae of Dorytomus cinereus Hochhuth (Coleoptera, Curculionidae) in Magadan Province, Russia - Konstantin G. Samartsev; Nikolai E. Dokuchaev (Journal of Insect Biodiversity and Systematics, 2024)
The data on biology and taxonomy of the new subspecies Bracon pallicarpus dorytomovorus Samartsev & Dokuchaev ssp. nov. are given. It was shown that in the Northern Okhotsk region, the wasps of the new subspecies are solitary univoltine parasitoids of the Dorytomus cinereus Hochhuth, 1851 (Coleoptera, Curculionidae) larvae which feed on the central axis of the catkins of the willow Salix rorida Lakschevitz (Salicaceae). Having consumed the weevil larva, the parasitoid forms a cocoon inside the host's tunnel and overwinters as a pupa inside the fallen catkin. Bracon pallicarpus dorytomovorus ssp. nov. adults emerge the next year in the second half of May. The status of the specimens of the type series of B. pallicarpus pallicarpus Thomson, 1892 was specified and its differences from 30 closely related species are presented. Bracon schmiedeknechti Fahringer, 1927 was synonymised with B. pallicarpus pallicarpus (syn. nov.).